Development of Catalytic Converter Learning Media to Improve Knowledge of Automotive Vocational School Students - Bambang Sudarsono (VANOS Journal of Mechanical Engineering Education, 2021)
Improving the quality of vocational high school graduates (SMK) is relevant to the needs of the world of work and industry. All teachers need support in preparing learning media that are by the competencies needed by the world of work and industry. This study aims to develop a catalytic converter exhaust emission system so that it can be used optimally to increase students' knowledge. The design study which is used in this research is a Four-D device development model which includes 4 stages of development, namely: the Define Stage, the Design Stage, the Development Stage, and the Disseminate Stage. The research subjects were students of class VII TKR in SMK Muhammadiyah 1 Salam, totalling 30 students. The stages of development are carried out properly to produce learning media an attractive and representative catalytic converter exhaust emission system so that it can significantly increase students' knowledge. There was an increase in students' knowledge using the learning media of the catalytic converter exhaust gas emission system as evidenced by the average pre-test score of 57.50% and the post-test result of 88.28% or an increase of 30.78%.